The Role of Work Teams in Enhancing the Employees’ Performance: An exploratory Study at the General Administration of the City of Medicine - Sawsan Ahmed Mahmoud Shukri; Amer Abdel Latif (Journal of Techniques)
The research aims to identify the role of work teams in enhancing the performance of workers in the General Administration of Medicine City, the Iraqi Ministry of Health. Where the city of medicine was chosen as a sample because there is a real problem to verify the hypotheses and objectives of this research. The research problem includes the organizations not adopting the work team’s style and its negative impact on the performance level of the employees. The questionnaire was adopted to collect the data, which consisted of two sides. The first side dealt with the personal data of the research sample employees, and the second side dealt with questions related to the two variables of the study (work teams and employee performance). Participated in the questionnaire survey (213) employees. The quantitative statistical method was used to analyze the data (such as Pearson correlation coefficient, simple linear regression method, arithmetic mean and standard deviation), depending on the (SPSS) program.  The research reached a set of results, including the existence of a close relationship between the work teams and the performance of the employees, which reflects the clear role of the performance of the employees through influencing the determination of the level of performance, Among the most prominent recommendations is the need for the organization’s management to adopt the research sample to develop human relations and teamwork spirit among employees.